First-principles study of point defects with different valences on the carrier activity, lifetime, absorption spectrum, and redox reaction of AlN (Li/Na/K) system. Issue 20 (18th October 2022) - Wang, Zhichao; Hou, Qingyu; Guan, Yuqin; Xu, Zhenchao; Zhao, Chunwang
ABSTRACT: Although the effects of Li/Na/K doping and point defect (VAl /VN ) coexistence on the physical properties of AlN systems have been reported, different valence state point defects (VAl 3–, 2–, 1–, 0 /VN 0, 3+ ) and the influence of H interstitial (Hi ) on the magnetic and photocatalytic properties of AlN systems are often neglected, and the experimental point defects (VAl /VN, Hi ) cannot be accurately controlled. This work uses first principle to study the influence of point defects with different valence states on the photocatalytic properties of the AlN system. Result showed that the formation energy ( Ef ) of the doped system is the smallest, and the stability is the best compared with all doped systems when the q of the Al35 LiHi N35 system is 1−. The absorption spectrum has an excellent red shift, an optimal carrier activity, a long carrier lifetime, and a strong redox ability. In summary, the photocatalytic performance of the doped system is the best when the q of the Al35 LiHi N35 system is 1−. This article lays the foundation for the research of new high-efficiency AlN photocatalytic materials.